Global Competitiveness of Riau Small and Medium Enterprise (SME) Special Food Products Entrepreneur in Pekanbaru, Sumatera, Indonesia - Ahmad Saleh; Afri Yordan; Nor Aishah Buang (Penerbit Kemala Indonesia, 2019)
In this globalization era, Indonesian entrepreneurs of SME food product need to be more competitive in order to growing some level in the entrepreneurs from other countries. The competitiveness of entrepreneurs is strongly required and emphasized by the government to growth the economy. Therefore, this study is conducted to identify category of global competitiveness of Riau SME special food products entrepreneur in Pekanbaru, Sumatera, Indonesia. This study also examine the differences between global competitiveness and education level of Riau SME special food products entrepreneur in Pekanbaru, Sumatra, Indonesia. The study is quantitative using a questionnaire instrument to 103 entrepreneurs from Riau SME special food products’ entrepreneurs in Pekanbaru. The findings show that the level of global competitiveness of SME entrepreneurs of Riau food products in Pekanbaru is at a moderate level (Min = 3.29, SP = 0.64). This means that the global competitiveness of SME entrepreneurs of Riau food products in Pekanbaru is categorized as neither high nor low. It indicates that Riau SME special food products’ entrepreneur in Pekanbaru have not competitiveness as recommended by the Indonesian government as well as they are not ready to face the increasingly competitive challenges of globalization. Therefore, to improve the level of competitiveness will need to improve the aspects that affect the competitiveness of the ability to explore market opportunities, ICT usage, innovation activities and self-development of entrepreneurs. The result of research also show that there is difference global competitiveness based on education level [F (3, 99) = 145.06, p = 0.00